Identification of Antibacterial Efficacy of Flavonoids of Anaegissus rotundifolia Against Some Pathogens: Identification of Antibacterial Efficacy of Flavonoids of Anaegissus rotundifolia Against Some Pathogens - Singariya, Dr. Premlata (International Journal of Pharmaceutical & Biological Archive, 2018)
Introduction: Antibacterial efficacy of flavonoids (bound and free) of different parts (root, stem, bark, flower, and gum) of Anaegissus rotundifolia was evaluated against seven bacteria (Bacillus subtilis = Gram-positive, Escherichia coli, Raoultella planticola, Enterobactor aerogens, Proteus mirabilis, Klebsiella pneumoniae, and Agrobacterium tumefaciens = Gram-negative bacteria). Material and Method: Flavonoids extracts of all the plant parts were found to possess strong antibacterial efficacy against these test pathogens, as revealed by zone of inhibition (ZOI [mm Â± standard deviation]), activity index (AI), minimum inhibitory concentration (MIC [mg/ml]), minimum bactericidal concentration (MBC [mg/ml]), and total activity (TA [ml/g]) of extracts against each sensitive test pathogens were also evaluated. All the pathogens were found to be sensitive against these flavonoid extracts. Result: Flavonoid extract of the root and stem showed the best activity against B. subtilis (Gram-positive bacteria), ZOI (16.50 Â± 0.24 mm), AI (1.100), MIC (0.078 mg/ml), and MBC (0.157 mg/ml). Highest TA (456.410 ml/g) of gum alkaloid was found against B. subtilis (G +ve bacteria). The findings of the present study suggested the exploitation of alkaloid extracts of Anaegissus rotundifolia for future antimicrobial drugs.